The Effect of Delayed Cord Clamping on Moderate and Early Late-Preterm Infants - Chiruvolu, Arpitha; Qin, Huanying; Nguyen, Elizabeth T.; Inzer, Robert W. (American Journal of Perinatology, 2018)
Objective This study aims to evaluate the clinical consequences of protocol-driven delayed umbilical cord clamping (DCC) implementation in moderate and early late-preterm (MELP) infants born between 320/7 and 346/7 weeks gestation.Study Design We conducted a prospective cohort study with a historic control cohort comparison. The prospective study period was 1 year when DCC was performed for 60 seconds duration (DCC cohort, n = 106). The study period for historic control cohort with no DCC was also 1 year before DCC implementation (historic cohort, n = 137).Results The mean hematocrit at birth was significantly higher in the DCC cohort compared with the historic cohort (49.1 ± 14.9 vs. 45.7 ± 15.7; p = 0.01). Fewer infants in the DCC cohort were admitted to neonatal intensive care unit (NICU) on respiratory support compared with the historic cohort (17.9 vs. 29.9%; p = 0.04). The incidence of respiratory distress syndrome was significantly lower in the DCC cohort compared with the historic cohort (2.8 vs. 14.6%; p = 0.002). There were no differences in the incidence of phototherapy or NICU length of stay (LOS) between groups.Conclusion In MELP infants, DCC was associated with increased hematocrit and better respiratory transition at birth. DCC was not associated with increased phototherapy or NICU LOS.
Keywords: delayed umbilical cord clamping; moderate and early late-preterm infants; neonatal intensive care unit; phototherapy; length of stay